Pengaruh Brand Image Terhadap Keputusan Pembelian Produk Pro Israel Dengan Kepuasan Konsumen Sebagai Variabel Mediasi Di Tengah Aksi Boikot Produk Pro Israel Dalam Perspektif Bisnis Islam : (Studi Pada Konsumen Aqua Di UIN RIl ) - Rahma Dayanti Syafitri; Weny Rosilawati (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Brand image is a very important factor in marketing management, the influence of brand image on purchasing decisions by considering the role of consumer satisfaction as a mediator, if the brand image of a company is strong it will increase consumer satisfaction, which in turn will influence consumer purchasing decisions. The formulation of the problem in this research is whether brand image influences purchasing decisions, whether brand image influences consumer satisfaction, whether consumer satisfaction influences purchasing decisions, whether consumer satisfaction can mediate the relationship between brand image and purchasing decisions. This research is quantitative research, the population in this research is students of the Faculty of Febi Uin Raden Intan Lampung. The sample used in this research was 100 respondents. Data collection uses a questionnaire. The data analysis technique used in this research is the SEM model using SmartPLS version 3.0. The research results obtained directly from each variable are that brand image has a positive and significant effect on purchasing decisions, brand image has a positive and significant effect on consumer satisfaction, consumer satisfaction has a positive and significant effect on purchasing decisions. And for the test results passing the mediating variable, it was found that consumer satisfaction was able to mediate the influence of brand image on purchasing decisions through partial mediation.